RELATIONSHIP OF KNOWLEDGE WITH OSTEOPOROSIS PREVENTION PREVENTED BY LANS IN WORKING AREA OF THREE RUNGGU HEALTH CENTER KECAMATAN PURBA, KABUPATEN SIMALUNGUN IN 2020 - Doortua, Doortua; Wooton, Ian; Wahyuni Tarigan, Sri; Syafrina, Efrin; Firdasari, Firdasari (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
Elderly who lack knowledge of osteoporosis and inadequate efforts have a higher risk for increasing the degree of osteoporosis, by increasing knowledge of the elderly about osteoporosis can prevent the increase in osteoporosis. The study wanted to examine the Relationship between Knowledge and Osteoporosis Prevention by the Elderly in the Work Area of the Tiga Runggu Public Health Center, Purba District, Simalungun Regency in 2020. The design of this study was a cross-sectional type of research conducted in August - October 2020. The population and samples in this study were Patients with diabetes mellitus in the work area of the Tiga Runggu Public Health Center, Purba District, Simalungun Regency in 2020, as many as 30 people. The majority of respondents had good knowledge, namely 18 people, while the minority had less knowledge, namely 12 people. The majority of osteoporosis prevention in good respondents was 17 people, while the prevention of osteoporosis in respondents was less, namely as many as 13 people. From the results of the cross-table chi-square test of knowledge with osteoporosis prevention, the p value is 0.035 <0.05. It can be concluded that knowledge has a relationship in the prevention of osteoporosis in the elderly in the work area of the Tiga Runggu Public Health Center, Purba District, Simalungun Regency in 2020. This study can provide guidelines and motivate osteoporosis clients in preventing and providing additional information for patients and their families to carry out control. For Puskesmas, this research provides input and benefits for health care institutions, especially in nursing to improve services in osteoporosis management, especially in maintaining the health conditions of the elderly with osteoporosis prevention efforts.